Review of Causes of Secondary Osteoporosis and Its Relationship with Fracture - Elif Umay Altaş; Şule Şahin Onat; İbrahim Bilir; Bengi Öz (Türk Osteoporoz Dergisi, 2020)

(untitled)
Objective:Osteoporosis (OP) is a skeletal disease characterised by low bone mass, which may occur due to primary or secondary reasons, and is known to increase the risk of fracture. The present study aimed to investigate the frequency and reasons for the diagnosis of secondary OP in patients presenting to our clinic and its relationship with fracture.Materials and Methods:Medical records of patients who came to our outpatient clinic with OP diagnosis were retrospectively reviewed. Demographic data (age, sex, etc.), comorbidities, drugs and fracture history of patients with secondary OP were obtained from the file information.Results:A total of 2,199 patients with OP were reviewed and 341 patients with secondary OP were included in the study. The most common causes of secondary OP were malignancy (38.4%), drug use (24.6%), rheumatologic diseases (17.3%). In addition, 94 patients had fractures and the mean age of these patients was statistically higher than those without fractures (p=0.008). Furthermore, the fracture rate was significantly higher in patients with chronic renal failure (CRF) (p= 0.034) and parathyroid adenoma (p=0.031) than those without these conditions.Conclusion:Causes of secondary OP and fracture rates were determined in patients with OP. Age was associated with CRF and parathyroid adenoma fracture rates. These situations should not be ignored while evaluating patients.